Use of luminometry and flow cytometry for evaluating the effects of cryoprotectants in the gorgonian coral endosymbiont Symbiodinium. Issue 4 (29th May 2019) - Lin, Chiahsin; Chong, Gabriella; Wang, Li‐Hsueh; Kuo, Fu‐Wen; Tsai, Sujune
SUMMARY: Cryopreservation has consistently proven to be a viable method for the storage of a wide variety of biological material, and there has been a recent focus on the cryopreservation of Symbiodinium spp. given the role of these dinoflagellates in the biology of the coral hosts with which they regularly associate. The present study aimed to identify the effect of various cryoprotectants (CPAs) on clade G Symbiodinium isolated from the whip coral Junceella fragilis by analyzing (i) dinoflagellate cell membrane integrity (via SYTOX® staining) and (ii) metabolic function (via an ATP assay) after cryopreservation. At low concentrations (1 M), none of the CPAs tested were harmful to the dinoflagellates at up to 60 min of incubation, and methanol and DMSO were the least harmful; neither caused a significant effect on cell ATP content even after 30 min incubations at 4 M concentrations. Detrimental effects of the CPAs increased in the following order: MeOH (lowest) = DMSO < EG < PG < Gly. With respect to the different assays, the ATP bioassay was more sensitive to CPA exposure than SYTOX staining. Given these findings, MeOH and DMSO should see more widespread use in cryopreservation protocols for clade G Symbiodinium, as well as other dinoflagellates.